Clopidogrel, Prasugrel or Ticagrelor in Patients with Acute Coronary Syndromes undergoing Percutaneous Coronary Intervention. - Yudi, M.; Clark, D.; Farouque, O.; Eccleston, D.; Andrianopoulos, N.; Duffy, S.; Brennan, A.; Lefkovits, J.; Ramchand, J.; Yip, T.; Oqueli, E.; Reid, Christopher; et al. (2016)
Background: Guidelines recommend prasugrel or ticagrelor instead of clopidogrel in patients with acute coronary syndromes (ACS) undergoing percutaneous coronary interventions (PCI). Aim: We sought to describe the trends in uptake of the newer agents and analyse the clinical characteristics and short-term outcomes of patients treated with clopidogrel, prasugrel or ticagrelor. Methods: We analysed the temporal trends of antiplatelet use since the availability of prasugrel (2009–2013) in patients with ACS from the Melbourne Interventional Group registry. To assess clinical characteristics and outcomes, we included 1850 patients from 2012 to 2013, corresponding to the time all three agents were available. The primary outcome was major adverse cardiovascular events (MACE). The safety end-point was in-hospital bleeding. Results: For the period of 2009–2013, the majority of patients were treated with clopidogrel (72%) compared with prasugrel (14%) or ticagrelor (14%). There was a clear trend towards ticagrelor by the end of 2013. Patients treated with clopidogrel were more likely to present with non-ST-elevation ACS, be older, and have more comorbidities. There was no difference in unadjusted 30-day mortality (0.9 vs 0.5 vs 1.0%, P = 0.76), myocardial infarction (2 vs 1 vs 2%, P = 0.52) or MACE (3 vs 3 vs 4%, P = 0.57) between the three agents. There was no difference in in-hospital bleeding (3 vs 2 vs 2%, P = 0.64). Conclusion Prasugrel and ticagrelor are increasingly used in ACS patients treated with PCI, predominantly in a younger cohort with less comorbidity. Although antiplatelet therapy should still be individualised based on the thrombotic and bleeding risk, our study highlights the safety of the new P2Y12 inhibitors in contemporary Australian practice.